Integrated Postsecondary Education Data System (IPEDS): Fall Enrollment Analysis, 1988 ([Verlag nicht ermittelbar], 1991)
The purpose of this data collection was to provide a more accurate measure the racial/ethnic enrollment in postsecondary institutions in the United States. The National Center for Education Statistics (NCES) collects racial/ethnic enrollment data from higher education institutions on a biennial basis. Some institutions do not report this data, and their "unknown" categories have previously been distributed in direct proportion to the "knowns." This resulted in lower than accurate figures for the racial/ethnic categories. With the advent of the Integrated Postsecondary Education Data System (IPEDS), NCES has attempted to eliminate this problem by distributing all race/ethnicity unknown students. This is done in a two-stage process. First, the differences between reported totals and racial/ethnic details are allocated on a gender and institutional basis by distributing the differences in direct proportion to reported distributions. The second stage distribution is designed to eliminate the remaining "race/ethnicity" unknowns. The procedure is to accumulate the reported racial/ethnic total enrollments by state, level, control, and gender, calculate the percentage distributions, and apply these percentages to the reported total enrollments of institutional respondents (in the same state, level, and control) that did not supply race/ethnicity detail. In addition, the original "race unknown" data were also left unaltered in order to provide data for those who wish to review numbers actually distributed. The racial/ethnic status was broken down into non-resident alien, Black non-Hispanic, American Indian or Alaskan Native, Asian or Pacific Islander, Hispanic, and White non-Hispanic. Variables include the educational level of all male/female full-time and part-time students enrolled in courses for credit at the institution. The unit of analysis is the postsecondary institution.